Anne of Avonlea - Montgomery, L.M. 1874-1942 (Montgomery, L.M. 1874-1942 (Lucy Maud) Anne of Green Gables novels, 2003)
In this sequel to "Anne of Green Gables," teenage Anne Shirley becomes a schoolteacher in a small village on Prince Edward Island.